Hydrogen sensor as well as preparation method and application thereof

By using a ceramic substrate electrode and coating a hydrophobic film on the surface of a semiconductor material doped with noble metals in a hydrogen sensor, the performance instability problem of the hydrogen sensor under high temperature and strong alkaline conditions was solved, and rapid and accurate hydrogen concentration monitoring was achieved.

CN121678779APending Publication Date: 2026-03-17SUZHOU NUCLEAR POWER RES INST CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511900134.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-12-16
Publication Date
2026-03-17

AI Technical Summary

Technical Problem

Existing hydrogen sensors are unstable in high-temperature, strong alkaline, and water environments, and cannot achieve real-time and accurate hydrogen concentration monitoring, resulting in response time differences and safety hazards.

Method used

The device employs a ceramic substrate electrode and a gas-sensitive layer. The gas-sensitive layer is a composite material formed by doping noble metals with semiconductor materials and coating a hydrophobic film on its surface. The hydrophobic film is formed by the chemical coupling reaction of hydrophobic silane and hydroxyl groups, providing corrosion resistance and protection.

Benefits of technology

Achieving rapid response and stable detection of hydrogen concentration in a high-temperature and strongly alkaline environment ensures the structural integrity and electronic transmission efficiency of the sensor, avoids the influence of environmental interference on the signal, and has a response time of less than 5 seconds.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121678779A_ABST
    Figure CN121678779A_ABST
Patent Text Reader

Abstract

The invention provides a hydrogen sensor as well as a preparation method and application thereof, and particularly relates to the technical field of sensors. The hydrogen sensor comprises a ceramic substrate electrode and a gas-sensitive layer, the gas-sensitive layer is arranged on the surface of the ceramic substrate electrode, the gas-sensitive layer comprises a composite material formed by doping a semiconductor material with precious metal, the surface of the composite material is coated with a hydrophobic membrane, and the surface of the hydrophobic membrane is coated with a metal layer. The hydrophobic membrane is formed by chemical coupling reaction of hydrophobic silane and hydroxyl groups. According to the hydrogen sensor, by adopting the specific semiconductor sensing material and the hydrophobic membrane, the adaptability and the stability of the hydrogen sensor in a high-temperature alkali liquor corrosion environment are greatly improved, the hydrogen sensor can reliably work for a long time in a severe environment, the replacement frequency of the sensor is reduced, and the use cost is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of sensor technology, and in particular to a hydrogen sensor, its preparation method, and its application. Background Technology

[0002] Hydrogen, as an important clean energy source and chemical raw material, has wide applications in many fields such as chemical synthesis, fuel cell development, and metal corrosion research. In these industrial production processes and scientific experiments, real-time and accurate monitoring of hydrogen concentration is crucial for ensuring production safety, improving product quality, and optimizing energy efficiency. Particularly in the alkaline water electrolysis hydrogen production process, monitoring the hydrogen concentration in the outlet gas of the electrolyzer not only affects the stability of the electrolysis process and the hydrogen production efficiency, but also directly impacts the safe operation of the system and the control of hydrogen purity.

[0003] However, in actual industrial applications of hydrogen production via alkaline water electrolysis, especially in-situ high-temperature alkaline water electrolysis, sensors often face the triple extreme challenges of high temperature, strong alkali, and aquatic environments. The performance limitations of existing hydrogen sensors are further amplified in these scenarios. From the perspective of core failure mechanisms: high-temperature environments easily cause irreversible microstructural damage to the sensor's sensitive material, disrupting the stable mechanism of hydrogen molecule adsorption and signal conversion, directly leading to fluctuations in sensing performance and making it difficult to maintain reliable detection accuracy; strong alkaline media cause continuous chemical corrosion on the surface of the sensitive material, damaging the integrity of the sensing interface and blocking the effective signal transmission path, making it impossible to achieve the goal of long-term stable detection of hydrogen concentration; in aquatic environments, water molecules easily adsorb onto the surface of the sensitive material, forming a water film that hinders effective contact between hydrogen and the sensitive layer, significantly reducing the sensor's response sensitivity.

[0004] More importantly, this performance degradation is directly reflected in the huge gap in monitoring response efficiency. Existing alkaline water electrolysis hydrogen production schemes based on non-in-situ monitoring generally have a monitoring delay of about 20 minutes, which cannot meet the needs of real-time safety early warning under extreme operating conditions. However, the core requirement for monitoring in in-situ high-temperature alkaline water electrolysis hydrogen production scenarios is to achieve a rapid response within seconds. The response time lag of existing technologies not only fails to reflect the dynamic changes in hydrogen concentration (such as sudden leaks) in a timely manner, but also amplifies the safety hazards such as hydrogen leaks and deflagrations in the high-risk environment of high temperature and strong alkalinity, which may lead to equipment damage, production shutdowns, or even personnel safety accidents.

[0005] Therefore, developing a hydrogen sensor that can operate stably for a long time in high-temperature and alkaline corrosive environments has significant practical implications and application value. Summary of the Invention

[0006] In view of the shortcomings of the prior art, the present invention provides a hydrogen sensor, its preparation method and application, to solve the technical problem of poor performance of existing hydrogen sensors in extreme environments such as high temperature and strong alkali.

[0007] To achieve the above and other related objectives, the present invention provides a hydrogen sensor, the hydrogen sensor comprising: a ceramic substrate electrode and a gas-sensitive layer, the gas-sensitive layer being disposed on the surface of the ceramic substrate electrode, wherein the gas-sensitive layer comprises a composite material formed by doping a semiconductor material with a noble metal, the surface of the composite material being coated with a hydrophobic film, the hydrophobic film being formed by a chemical coupling reaction between a hydrophobic silane and hydroxyl groups.

[0008] In one embodiment of the present invention, the semiconductor material includes one or more of molybdenum disulfide, tin dioxide, titanium dioxide, zinc oxide, and indium oxide.

[0009] In one embodiment of the present invention, the precious metal includes one or more of ruthenium, gold, palladium, and platinum.

[0010] In one embodiment of the present invention, the doping amount of the noble metal accounts for 0.1 wt% to 5 wt% of the mass of the semiconductor material.

[0011] In one embodiment of the present invention, the hydrophobic silane includes one or more of vinyltrimethoxysilane and vinyltriethoxysilane; and / or, the contact angle of the hydrophobic membrane is greater than or equal to 90°, and the coating thickness of the hydrophobic membrane is 0 to 2 μm.

[0012] In one embodiment of the present invention, the hydrogen sensor further includes a housing, which encapsulates the ceramic substrate electrode and the gas-sensitive layer.

[0013] The present invention also provides a method for preparing a hydrogen sensor, the method comprising the following steps:

[0014] Semiconductor material is dispersed in a solvent, a noble metal salt solution is added and stirred, so that noble metal ions are adsorbed on the surface of the semiconductor material. After solid-liquid separation and drying, a first precursor is obtained.

[0015] The first precursor is subjected to hydroxylation treatment to introduce hydroxyl groups on the surface of the first precursor to obtain a second precursor;

[0016] The second precursor was transferred to a hydrophobic silane solution, the pH of the system was adjusted to alkaline, and the reaction was stirred to allow the hydrophobic silane to react with the hydroxyl groups, thereby obtaining a gas-sensitive material precursor coated with a hydrophobic film.

[0017] The gas-sensitive material precursor coated with the hydrophobic film is calcined in a reducing atmosphere to reduce the noble metal ions and solidify the hydrophobic film, thereby obtaining the gas-sensitive material coated with the hydrophobic film.

[0018] The gas-sensitive material coated with the hydrophobic film is formulated into a slurry and coated onto the surface of a ceramic substrate electrode to obtain a hydrogen sensor.

[0019] In one embodiment of the present invention, the hydroxylation treatment includes any one of plasma treatment, alkaline treatment, and hydrothermal method.

[0020] In one embodiment of the present invention, the solvent includes an organic solvent and / or deionized water, wherein the organic solvent includes one or more of ethanol, acetonitrile, and isopropanol.

[0021] In one embodiment of the present invention, in the step of calcining the hydrophobic membrane-coated gas-sensitive material precursor in a reducing atmosphere, the reducing atmosphere is a mixture of hydrogen and nitrogen, wherein the volume percentage of hydrogen in the mixture is 1-30%, the reduction temperature is 100-500°C, and the reduction time is 4-12 hours.

[0022] The present invention also provides an application of a hydrogen sensor, which is used for hydrogen monitoring under extreme conditions of high temperature and strong alkali. The hydrogen detection concentration range of the hydrogen sensor is 0 to 5 vol%, and the hydrogen detection temperature is 2 to 120°C.

[0023] The beneficial effects of this invention are as follows: The hydrogen sensor proposed in this invention constructs highly efficient hydrogen adsorption active sites and optimizes electron transport efficiency by doping noble metals onto the surface of semiconductor materials. Simultaneously, a hydrophobic film provides stable protection for the gas-sensitive layer, avoiding the influence of environmental interference on the sensing signal and ensuring the accuracy and reliability of the detection results. The hydrophobic film is formed on the surface of the gas-sensitive material through in-situ growth. It effectively isolates corrosive media such as moisture and alkaline solutions from intrusion, protecting the structural integrity and electron transport efficiency of the gas-sensitive layer. Furthermore, the nanoscale hydrophobic molecular pores formed on the film surface ensure selective permeation of hydrogen molecules, avoiding the obstruction of sensing performance by traditional protective structures and achieving efficient synergy between protection and sensing.

[0024] The hydrogen sensor of this invention has excellent adaptability to extreme environments and can accurately adapt to the requirements of high temperature and strong alkaline conditions. It can operate stably in a temperature range of 2 to 120°C and can withstand alkaline environments such as potassium hydroxide, sodium hydroxide, sodium carbonate, and sodium bicarbonate with a mass fraction of 0 to 50% (corresponding to a strong alkaline range of pH 8 to 14). It effectively solves the performance degradation problems of traditional hydrogen sensors, such as irreversible damage to the microstructure of sensitive materials caused by high temperature, surface chemical corrosion caused by strong alkali, and water film formation in aqueous environments that hinders the adsorption of hydrogen molecules. It meets the long-term monitoring needs in extreme scenarios such as alkaline water electrolysis for hydrogen production. Attached Figure Description

[0025] The accompanying drawings, which are incorporated in and form part of this specification, illustrate embodiments consistent with this application and, together with the description, serve to explain the principles of this application. It is obvious that the drawings described below are merely some embodiments of this application, and those skilled in the art can obtain other drawings based on these drawings without any inventive effort.

[0026] In the attached diagram:

[0027] Figure 1 This is a schematic diagram of the structure and connection of each functional layer of a hydrogen sensor provided in one embodiment of the present invention;

[0028] Figure 2 This is a schematic diagram of the hydrophobic structure of the gas-sensitive layer material provided in one embodiment of the present invention;

[0029] Figure 3 This is a scanning electron microscope (SEM) image of molybdenum disulfide provided in one embodiment of the present invention;

[0030] Figure 4 This is a projection electron microscope (TEM) image of molybdenum disulfide provided in one embodiment of the present invention;

[0031] Figure 5 This is a microporous structure on the surface of a hydrophobic membrane provided in one embodiment of the present invention;

[0032] Figure 6 The contact angle of the hydrophobic membrane is provided in one embodiment of the present invention;

[0033] Figure 7 This is a physical image of a hydrogen sensor provided in one embodiment of the present invention;

[0034] Figure 8 This is a flowchart of a method for preparing a hydrogen sensor according to an embodiment of the present invention;

[0035] Figure 9 This is a schematic diagram of a hydrogen sensor detection system provided in one embodiment of the present invention;

[0036] Figure 10 This is the test performance data of a hydrogen sensor in one embodiment of the present invention.

[0037] The attached figures are labeled as follows:

[0038] 100. Hydrogen sensor; 110. Ceramic substrate electrode; 111. Ceramic substrate; 112. Electrode; 113. Heating wire; 120. Gas-sensitive layer; 121. Composite material formed by doping semiconductor material with noble metals; 122. Hydrophobic film. Detailed Implementation

[0039] The following specific examples illustrate the implementation of the present invention. Those skilled in the art can easily understand other advantages and effects of the present invention from the content disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments. Various details in this specification can also be modified or changed based on different viewpoints and applications without departing from the spirit of the present invention. In the absence of conflict, the following embodiments and features in the embodiments can be combined with each other.

[0040] It should be noted that the illustrations provided in the following embodiments are only schematic representations of the basic concept of the present invention. The drawings only show the components related to the present invention and are not drawn according to the actual number, shape and size of the components in the actual implementation. In the actual implementation, the form, quantity and proportion of each component can be arbitrarily changed, and the layout of the components may also be more complex.

[0041] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the description of the invention is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention.

[0042] The terms or phrases used in this article have the following meanings:

[0043] In this article, the terms "multiple," "various," and "multiple times" are used unless otherwise specified, referring to a quantity greater than or equal to 2. For example, "one or more" means one or more types.

[0044] In this document, terms such as “preferred,” “ideal,” “further,” “even more,” and “particularly” are used for descriptive purposes to indicate differences in content, but should not be construed as limiting the scope of protection of this invention.

[0045] In this document, when referring to numerical ranges, unless otherwise specified, the distribution of selectable values ​​within a numerical range is considered continuous, including the two endpoints of the range (i.e., the minimum and maximum values), and every value between these two endpoints. When multiple numerical ranges are provided to describe a feature or property, these numerical ranges can be combined.

[0046] This invention provides a hydrogen sensor, a method for preparing the hydrogen sensor, and an application of the hydrogen sensor. Through a synergistic technical solution of optimizing the composition of the gas-sensitive material and precisely designing the multilayer structure of the hydrophobic film, the hydrogen concentration can be accurately and rapidly detected in high-temperature and strongly alkaline solution environments, solving the problem of poor performance of existing hydrogen sensors in harsh environments.

[0047] Please see Figure 1The hydrogen sensor 100 provided by the present invention includes a ceramic substrate electrode 110 and a gas-sensitive layer 120. The ceramic substrate electrode 110 is the basic support and signal transmission carrier of the sensor, and the gas-sensitive layer 120 is the core of the sensor to realize the conversion of "hydrogen concentration → electrical signal".

[0048] Specifically, the ceramic substrate electrode 110 includes a ceramic substrate 111 and an electrode 112. The ceramic substrate 111 serves as the base structure of the sensor, providing support and insulation, and providing a mounting carrier for other components. In some optional embodiments, the ceramic substrate 111 is made of insulating ceramic, such as alumina ceramic or zirconia ceramic. On the one hand, ceramic materials possess excellent high-temperature resistance (withstanding temperatures above 200°C) and alkali corrosion resistance (not reacting chemically with alkaline solutions such as potassium hydroxide and sodium hydroxide), allowing them to maintain structural integrity for extended periods under extreme conditions. On the other hand, the high insulation of ceramics prevents signal interference between electrodes, ensuring accurate transmission of electrical signals generated by hydrogen molecule adsorption. The shape of the ceramic substrate 111 is not limited here and can be selected according to actual conditions. For example, the ceramic substrate 111 can be a tubular structure or a sheet structure. The electrode 112 is integrated on the surface of the ceramic substrate 111, serving to collect electrical signals and improve sensing sensitivity. The material of the electrode 112 can be platinum (Pt), gold (Au), or their alloys (such as Pt-Au). Furthermore, the electrode 112 can be any electrode form that can be used in a hydrogen sensor, such as an interdigitated electrode, a parallel electrode, or a spiral electrode.

[0049] Furthermore, the ceramic substrate electrode 110 also includes a heating wire 113, which provides the temperature environment required for the operation of the hydrogen sensor 100, ensuring that the gas-sensitive material performs at a suitable temperature. For example, the ceramic substrate 111 is a ceramic tube, and the heating wire 113 is spirally disposed inside the ceramic tube; the heating wire 113 may be, for example, a nickel-cadmium alloy wire.

[0050] Please see Figures 1 to 5 A gas-sensitive layer 120 is disposed on the surface of the ceramic substrate electrode 110, meaning the gas-sensitive layer 120 is tightly attached to the surfaces of the ceramic substrate 111 and the electrode 112. When hydrogen reacts with the gas-sensitive layer 120, it causes changes in the electrical properties of the gas-sensitive material, such as resistance and capacitance. The electrode 112 quickly captures these electrical changes and converts them into measurable electrical signals, thereby enabling the detection of hydrogen concentration. In this application, the gas-sensitive layer 120 includes a composite material 121 formed by doping a semiconductor material with noble metals, and the surface of this composite material is coated with a hydrophobic film 122. The composite material 121 formed by doping a semiconductor material with noble metals serves as the core material of the gas-sensitive layer 120, enabling hydrogen molecule adsorption, while the hydrophobic film 122 is a protective layer that isolates corrosive media and ensures hydrogen molecule permeation.

[0051] In some embodiments, the semiconductor material includes one or more of molybdenum disulfide (MoS2), tin dioxide (SnO2), titanium dioxide (TiO2), zinc oxide (ZnO), and indium oxide (In2O3). These semiconductor materials possess a large specific surface area, providing abundant adsorption sites, and excellent interlayer electron transport performance, enabling rapid electron transfer after hydrogen molecule adsorption. Simultaneously, they exhibit high chemical stability, are not prone to phase transitions at high temperatures, and ensure stable sensing performance. The semiconductor materials listed above can be used individually or in combination. For example, the semiconductor material may be molybdenum disulfide, tin dioxide, a combination of titanium dioxide and zinc oxide, or a combination of molybdenum disulfide, tin dioxide, and indium oxide, etc. It should be noted that when semiconductor materials are used in combination, the proportions of the components within the composition are not limited and can be combined in any proportion. Preferably, molybdenum disulfide is selected as the semiconductor material; see [link to relevant documentation]. Figure 3 and Figure 4 Molybdenum disulfide has a layered structure, which not only provides ample space for noble metal doping but also accelerates signal conversion through interlayer electron transport channels, further improving response speed. Noble metals are dispersed on the surface of semiconductor materials in an atomic-level doping manner, constructing highly efficient hydrogen adsorption active sites. Compared to the semiconductor material itself, noble metal atoms have a stronger adsorption affinity for hydrogen molecules, significantly improving the adsorption efficiency of hydrogen molecules. Simultaneously, as excellent conductors, noble metals can form electron transport channels within the semiconductor substrate, accelerating the transfer rate of electrons after hydrogen molecule adsorption, thereby improving the sensor's response sensitivity and response speed, achieving a response time of <5 seconds. In some embodiments, the noble metal includes one or more of ruthenium, gold, palladium, and platinum; for example, the noble metal may be ruthenium, gold, or a combination of platinum and palladium, etc. The higher the noble metal doping concentration, the more noble metal atoms are dispersed on the surface of the semiconductor material, resulting in a higher density of hydrogen adsorption active sites. This makes it easier for hydrogen molecules to be captured and creates denser electron transport channels, leading to higher detection accuracy and a more stable response. Conversely, lower noble metal doping concentrations result in insufficient active site density, lower hydrogen molecule adsorption efficiency, and increased susceptibility to electron transport path interference, leading to increased detection errors and decreased response stability. There is no specific limitation on the noble metal doping concentration; it can be rationally selected based on actual needs. In some embodiments, the noble metal doping concentration accounts for 0.1 wt% to 5 wt% of the semiconductor material mass. For example, the noble metal doping concentration can be 0.1 wt%, 1 wt%, 3 wt%, or 5 wt%, etc.

[0052] Please see Figure 2 and Figure 5The hydrophobic film 122 is formed through a chemical coupling reaction between hydrophobic silane and hydroxyl groups. Specifically, the composite material 121, formed by doping noble metals with semiconductor materials, undergoes hydroxylation treatment, resulting in a large number of hydroxyl groups on its surface. The alkoxy groups (-OCH3 / -OC2H5) in the hydrophobic silane molecules undergo hydrolysis to generate silanol groups (-Si-OH). These silanol groups then undergo a dehydration condensation reaction with the hydroxyl groups on the surface of the composite material, forming covalent bonds between Si and O materials. Simultaneously, self-condensation also occurs between the silanol groups to form a Si-O-Si cross-linked structure, resulting in a structure resembling... Figure 5 The mesh structure shown forms a uniform and dense hydrophobic film 122 on the surface of the composite material.

[0053] In some embodiments, the hydrophobic silane includes one or more of vinyltrimethoxysilane and vinyltriethoxysilane. For example, the hydrophobic silane is vinyltrimethoxysilane, or vinyltriethoxysilane, or a composition of vinyltrimethoxysilane and vinyltriethoxysilane mixed in any proportion. Of course, the hydrophobic silane may also be any hydrophobic material not listed above that can react in situ with hydroxyl groups.

[0054] In some embodiments, the thickness of the hydrophobic film 122 is controlled between 0 and 2.0 μm; further, the thickness of the hydrophobic film 122 is between 0.5 and 1.5 μm; and even further, the thickness of the hydrophobic film is 1.0 μm. If the hydrophobic film 122 is too thick, it will hinder the permeation of hydrogen molecules; if it is too thin, it will not effectively isolate the corrosive medium.

[0055] Please see Figure 6 In some embodiments, the contact angle of the hydrophobic membrane 122 is ≥90°, and further, the contact angle is 120° to 150°, specifically 120°, 130°, 140°, or 150°, etc. A high contact angle ensures that water molecules and alkaline solutions cannot spread on the membrane surface, avoiding the formation of a water film or corrosion. Simultaneously, the nanoscale pores formed on the surface of the hydrophobic membrane 122 allow hydrogen molecules to selectively permeate to the underlying composite material surface, achieving synergistic optimization of protection (isolation of alkaline solutions and moisture) and sensing (hydrogen molecule adsorption).

[0056] Those skilled in the art will recognize that the hydrogen sensor 100 also includes essential technical features, such as a housing, see [link to relevant documentation]. Figure 7 The outer casing is used to encapsulate the ceramic substrate electrode 110 and the gas-sensitive layer 120. The structures in the hydrogen sensor 100 not described in detail above can all be set according to conventional structures in the art, and will not be described in detail here.

[0057] Please see Figure 8 The present invention also provides a method for preparing a hydrogen sensor, the method comprising the following steps:

[0058] S1. Disperse the semiconductor material in a solvent, add a noble metal salt solution and stir, so that the noble metal ions are adsorbed on the surface of the semiconductor material. After solid-liquid separation and drying, the first precursor is obtained.

[0059] S2. The first precursor is subjected to hydroxylation treatment to introduce hydroxyl groups on the surface of the first precursor to obtain the second precursor.

[0060] S3. The second precursor is transferred to a hydrophobic silane solution, the pH of the system is adjusted to alkaline, and the reaction is stirred to allow the hydrophobic silane to react with the hydroxyl groups, thereby obtaining a gas-sensitive material precursor coated with a hydrophobic film.

[0061] S4. The gas-sensitive material precursor coated with hydrophobic film is calcined in a reducing atmosphere to reduce the noble metal ions and solidify the hydrophobic film to obtain the gas-sensitive material coated with hydrophobic film.

[0062] S5. Prepare a slurry by coating the hydrophobic film-coated gas-sensitive material onto the surface of the ceramic substrate electrode to obtain a hydrogen sensor.

[0063] Specifically, the semiconductor material in step S1 includes, but is not limited to, one or more of molybdenum disulfide, tin dioxide, titanium dioxide, zinc oxide, and indium oxide. The solvent is mainly used to disperse the semiconductor material and can be an organic solvent, deionized water, or a mixture of an organic solvent and deionized water. Further, the organic solvent includes one or more of ethanol, acetonitrile, and isopropanol; for example, the organic solvent may be ethanol, acetonitrile, or a combination of isopropanol and ethanol, etc. The ratio of semiconductor material to solvent is not limited, as long as the semiconductor material is evenly dispersed. Dispersion methods include ultrasonic dispersion, magnetic stirring, etc. Furthermore, to improve the dispersion effect of the semiconductor material in the solvent, surfactants may be added, such as hexadecyltrimethylammonium bromide (CTAB), sodium dodecylbenzenesulfonate (SDBS), Tween-80, etc.

[0064] After the semiconductor material is uniformly dispersed in the solvent to form a homogeneous liquid, a noble metal salt solution is added, and a homogeneous solution is obtained using a magnetic stirrer or other stirring device. During stirring, noble metal ions adsorb onto the surface of the semiconductor material. The type of noble metal salt is selected according to the type of noble metal to be doped. For example, if the noble metal is gold, chloroauric acid can be selected; if the noble metal is ruthenium, ruthenium chloride can be selected; if the noble metal is platinum, platinum chloride can be selected; if the noble metal is palladium, palladium chloride can be selected, and so on. The concentration and amount of the noble metal salt solution directly determine the final doping amount of the noble metal and can be selected according to the actual situation. In some embodiments, the doping amount of the noble metal accounts for 0.1wt% to 5wt% of the semiconductor material mass, for example, 0.1wt%, 1wt%, 3wt%, or 5wt%, etc. The concentration and amount of the noble metal salt solution can be calculated based on the doping amount of the noble metal.

[0065] Subsequently, a centrifuge is used to separate the solid material from the solvent in the above solution, removing the supernatant liquid, and the obtained solid is then vacuum dried. For example, the vacuum drying temperature is 50–100°C, such as 50°C, 80°C, or 100°C, etc., and the drying time is not specifically limited, as long as complete drying is achieved. For example, drying time is 6–24 hours, such as 6 hours, 12 hours, 16 hours, or 24 hours, etc. After drying, a first precursor of a semiconductor material composite with noble metal ions adsorbed on its surface is obtained.

[0066] Step S2 involves hydroxylating the first precursor obtained in step S1 using plasma treatment. The specific process is as follows: the reaction chamber of the plasma cleaner is evacuated to a vacuum state to eliminate interference from impurity gases on the surface treatment; then, the first precursor powder prepared in step S1 is placed in the plasma cleaner, and a working medium is introduced into the plasma cleaner. Under the action of plasma, the surface of the first precursor powder is activated. This process can break some inert bonds on the surface of the semiconductor material, thereby introducing a large number of hydroxyl (-OH) groups onto the material surface, resulting in a surface-functionalized second precursor, providing reaction sites for the subsequent surface chemical coupling of the hydrophobic film. In some embodiments, the working medium during plasma treatment is selected from compressed air, oxygen, or argon. Preferably, argon is used as the working medium, as it has the highest efficiency in introducing hydroxyl groups onto the material surface. In other embodiments, the hydroxylation treatment can also be performed using hydrothermal treatment or alkaline treatment, etc.

[0067] Step S3 involves transferring the surface-functionalized second precursor obtained in step S2 into an aqueous silane solution, adding an alkaline solution to adjust the system to an alkaline environment, and continuously stirring under magnetic stirring for 10 to 60 minutes, for example, 10 minutes, 30 minutes, or 60 minutes, so that the hydrophobic silane molecules in the solution undergo a chemical coupling reaction with the hydroxyl groups on the surface of the second precursor, forming a uniform and stable alkali-resistant hydrophobic layer on its surface.

[0068] Hydrophobic silanes include, but are not limited to, vinyltrimethoxysilane and / or vinyltriethoxysilane. Sodium hydroxide solution can be used to adjust the pH of the system, with a pH value ranging from 8 to 14, specifically 9, 10, 12, or 14. Alkaline conditions catalyze the hydrolysis of the alkoxy groups in the hydrophobic silane molecules, where the alkoxy group (-OCH3 / -OC2H5) is replaced by a water molecule to generate a silanol group (-Si-OH), simultaneously releasing alcohol byproducts (such as methanol / ethanol).

[0069] Taking vinyltrimethoxysilane as an example:

[0070] CH2=CH-Si-(OCH3)3+3H2O (alkaline)→CH2=CH-Si-(OH)3+3CH3OH

[0071] This step is a prerequisite for the subsequent condensation reaction. The silanol group (-Si-OH) is the reactive site and can undergo dehydration condensation with the hydroxyl group (-OH).

[0072] Next, the directional condensation of silanol groups with hydroxyl groups on the material surface achieves in-situ bonding: the silanol groups (-Si-OH) generated by the hydrolysis of hydrophobic silane undergo a dehydration condensation reaction with the hydroxyl groups (-OH) on the surface of the second precursor, removing one water molecule to form a covalent bond of Si-O- material; this covalent bond directly "anchors" the hydrophobic silane molecules to the surface of the gas-sensitive material, achieving in-situ growth of chemical coupling.

[0073] In addition to reacting with hydroxyl groups on the material surface, silanol groups also undergo dehydration condensation reactions between silanol groups (-Si-OH) generated from the hydrolysis of different hydrophobic silane molecules: the silanol groups (-Si-OH) of adjacent silane molecules lose water molecules to form Si-O-Si covalent bonds, causing the silane molecules to crosslink with each other, gradually forming a continuous and uniform network structure (such as...). Figure 5 (As shown). This cross-linked structure ultimately forms a uniform and dense hydrophobic film, which can both isolate high-temperature alkaline solutions / moisture and ensure high-temperature and alkali resistance through the stability of Si-O-Si bonds. After step S3, the gas-sensitive material precursor coated with the hydrophobic film is obtained.

[0074] Next, step S4 is performed, in which the gas-sensitive material precursor coated with hydrophobic film obtained in step S3 is calcined in a reducing atmosphere to reduce the noble metal ions to noble metals, while simultaneously curing the hydrophobic film to obtain the gas-sensitive material coated with hydrophobic film.

[0075] In this step, the reducing atmosphere is a mixture of hydrogen (H2) and nitrogen (N2), with hydrogen accounting for 1-30% of the volume. The reduction temperature is set to 100-500℃, and the reduction time is set to 4-12 hours. Specific parameters can be adjusted according to the crystallinity requirements of the gas-sensitive material. For example, the reducing atmosphere can be an H2 / N2 mixture with 10% H2, 20% H2, or 30% H2, etc. The reduction temperature can be 100℃, 300℃, or 500℃, etc.; the reduction time can be 4 hours, 8 hours, or 12 hours, etc. After calcination, a hydrophobic film-coated gas-sensitive material is obtained.

[0076] Next, in step S5, the gas-sensitive material coated with the water-membrane is prepared into a slurry. The preparation process can refer to conventional procedures in the art. For example, 0.1 mg of the obtained gas-sensitive material is taken, and 2 μl of ethylene glycol solution is added dropwise while grinding. The mixture is ground until a fine and uniform slurry is obtained. The slurry is then coated onto the surface of a ceramic substrate electrode, and after drying, a hydrogen sensor is obtained.

[0077] In some embodiments, after step S5, an assembly step is also included, in which the base gas-sensitive material with a hydrophobic film is assembled into the housing to obtain the hydrogen sensor resistant to high-temperature alkaline corrosion.

[0078] The hydrogen sensor prepared by this invention has a hydrogen detection concentration range of 0–5 vol% and a hydrogen detection temperature range of 2–120°C. Furthermore, this hydrogen sensor can operate normally in an alkaline environment containing sodium hydroxide, potassium hydroxide, sodium carbonate, and sodium bicarbonate, with the alkaline solution having a mass fraction range of 0–50%. After immersing the hydrogen sensor in an alkaline solution with a mass fraction of 10%–50% for 0–5000 hours, the hydrophobic properties of the hydrophobic film still maintain a contact angle greater than 120°. After immersing in an alkaline solution with pH=14 for 168 hours, the overall performance remains stable. In a high humidity environment with humidity greater than 80%, the error of the detection data does not exceed ±2%.

[0079] The hydrogen sensor of this invention has a wide detection range, capable of detecting hydrogen gas in the concentration range of 0–5 vol%, with an operating temperature range of 2–120°C. It can operate normally in 0–50% potassium hydroxide solution (corresponding to a strongly alkaline environment with pH 8–14). Furthermore, this hydrogen sensor possesses rapid response and recovery characteristics, with a hydrogen detection response time of less than 5 seconds and a recovery time of less than 10 seconds, enabling it to reflect changes in hydrogen concentration promptly and accurately. This wide-range hydrogen detection capability, along with its rapid response and recovery time, allows the sensor to monitor changes in hydrogen concentration in a timely and accurate manner, providing reliable data support for related production processes and experiments, and contributing to improved production safety and the accuracy of experimental results.

[0080] The present invention also provides an application of the above-mentioned hydrogen sensor, which can be used for hydrogen monitoring under extreme conditions of high temperature and strong alkali, such as in the alkaline water electrolysis hydrogen production industry, alkaline fuel cells, chlor-alkali industry and other industrial fields.

[0081] The technical solution of the present invention will be described in detail below through several specific embodiments and comparative examples. Unless otherwise stated, the raw materials and reagents used in the following embodiments are all commercially available products, or can be prepared by conventional methods in the art, and the instruments used in the embodiments are all commercially available.

[0082] Example 1

[0083] This embodiment provides a hydrogen sensor, the fabrication process of which is as follows:

[0084] (1) MoS2, with its high surface area and excellent interlayer electron transport properties, was selected as the semiconductor sensitive material substrate. 0.2 g of MoS2 powder was mixed into an ethanol solution containing 60 mg of surfactant (CTAB). The mixed solution was dispersed at 45°C for 60 min using an ultrasonic disperser to obtain a MoS2-layers dispersion. Then, 2.03 ml of 1 mM RuCl3 solution was added to the dispersion, and the mixture was continuously stirred at room temperature to allow RuCl3 to dissolve. 3+ Ions were uniformly adsorbed on the surface of the MoS2 layer; then the dispersion was transferred to a centrifuge, and the solid powder in the dispersion was separated from the liquid by centrifugal force. The supernatant liquid was removed, the solid product was collected and vacuum dried to obtain Ru. 3+ @MoS2 solid powder;

[0085] (2) Evacuate the plasma cleaning machine's reaction chamber to a vacuum state to eliminate interference from impurity gases on the surface treatment; then, the Ru prepared in step (1) is... 3+@MoS2 powder was placed in a plasma cleaner, and then a high-purity inert gas (argon) was introduced into the plasma cleaner as a working medium. The Ru powder was then subjected to plasma treatment. 3+ The surface of MoS2 powder is activated, which breaks some of the inert bonds on the MoS2 surface, thereby introducing a large number of hydroxyl (-OH) groups into the material surface, resulting in surface-functionalized Ru. 3+ @MoS2-OH provides reaction sites for subsequent surface chemical coupling of hydrophobic films.

[0086] (3) The surface-activated Ru 3+ @MoS2-OH powder was immediately transferred to a vinyltrimethoxysilane solution, and NaOH solution was added to adjust the pH to 14. The reaction was continued for about 30 minutes under magnetic stirring, allowing the hydrophobic silane molecules in the solution to react with Ru. 3+ The hydroxyl groups on the surface of @MoS2-OH undergo a dehydration condensation reaction, achieving chemical coupling and forming a uniform, dense, and strongly bonded high-temperature and alkali-resistant hydrophobic film on its surface, yielding the gas-sensitive material precursor Ru. 3+ @MoS2-Si.

[0087] (4) Take the Ru obtained in step (3) 3+ The MoS2-Si precursor powder was washed with distilled water to remove unreacted silane impurities. The washed sample was then placed in a tube furnace and calcined at 250°C for 2 hours under a hydrogen-nitrogen mixed atmosphere (hydrogen volume percentage 30%) to complete the Ru... 3+ The Ru@MoS2-Si gas-sensitive material was obtained by reducing metallic Ru and curing the hydrophobic film.

[0088] (5) Take 0.1 mg of the gas-sensitive material obtained in step (4), and add 2 μl of ethylene glycol solution dropwise while grinding. Grind until a fine and uniform slurry is obtained. Coat the slurry onto the surface of the ceramic substrate electrode (coating thickness 5 μm), and then heat it in a 60℃ oven for 48 hours to remove the solvent and enhance the bonding force between the material and the electrode, thus obtaining an ultrasensitive hydrogen gas sensor resistant to high-temperature alkaline corrosion. Among them, the ceramic substrate electrode uses insulating ceramic as the substrate and integrates a pair of interdigital electrodes for current signal acquisition and output. The overall structure is compact and conducive to miniaturization and integration.

[0089] The high-temperature alkaline corrosion resistant hydrogen sensor prepared in Example 1 was tested by an ellipsometry, and the uniformity deviation of the hydrophobic film was ±4.2%; the surface contact angle was measured by a contact angle meter and found to be 153°.

[0090] The sample was placed in a 200℃ oven for 700 hours for continuous aging. After removal, the contact angle was still 153°, indicating that the hydrophobic film has excellent high temperature resistance. The sample was immersed in a NaOH solution with a pH of 14 at a depth of 2m for 168 hours. After removal, the hydrophobic film did not crack or fall off, and the contact angle remained at 148°.

[0091] Please see Figure 9 and Figure 10 The hydrogen sensor prepared in Example 1 was applied to monitor the hydrogen production concentration in real time during the alkaline water electrolysis process. Figure 9 This system is designed to simulate the hydrogen production process through water electrolysis. Specifically designed for extreme high-temperature and strong alkaline conditions, it can reproduce the hydrogen generation environment at the electrolyzer outlet during alkaline water electrolysis (such as high temperature, alkaline evaporation atmosphere, and dynamic changes in hydrogen concentration), avoiding the disconnect between static laboratory testing and actual industrial scenarios. Figure 10 The horizontal axis represents hydrogen concentration, and the vertical axis represents the sensor's response value or response error. The data shows that the sensor has a response error of ≤±1.2% in the hydrogen concentration range of 0 to 5 vol%, and its performance does not fluctuate significantly in the detection temperature range of 2 to 120℃. The concentration and response value show a good linear or stable correspondence with no obvious data dispersion.

[0092] Example 2

[0093] This embodiment is similar to Embodiment 1, except that the type of noble metal doped is changed. In step (1), 0.25 ml of 1 mM HAuCl4 solution is added to construct adsorption active sites through gold (Au) atom doping. The remaining steps are performed in accordance with Embodiment 1.

[0094] The high-temperature alkali corrosion resistant hydrogen sensor prepared in Example 2 showed a uniformity deviation of ±4.8% as measured by an ellipsometry; the surface contact angle was 145°; after being placed at 200°C for 700 hours, the contact angle decreased to 142° with no significant performance degradation, demonstrating good high-temperature stability; when the hydrogen sensor was immersed in a NaOH solution with a depth of 2m and pH=14 for 168 hours, the hydrophobic film remained intact, and the contact angle remained at 125°.

[0095] The hydrogen sensor was applied to monitor the hydrogen production concentration in real time during the alkaline water electrolysis process. The sensor has a detection error of ≤±1.5% within the detection range of 0-5 vol% H2, and a response time fluctuation of ≤0.3s within the detection temperature range of 2-120℃, demonstrating stable dynamic response characteristics.

[0096] Example 3

[0097] This embodiment is similar to Embodiment 1, except that the type of silane precursor for the hydrophobic film is adjusted, that is, in step (3), the treated Ru...3+ @MoS2-OH powder was immediately transferred to a vinyltriethoxysilane solution, and a hydrophobic protective layer was constructed through the hydrolysis and condensation reaction of vinyltriethoxysilane. The remaining steps were carried out in accordance with Example 1.

[0098] The high-temperature alkaline corrosion resistant hydrogen sensor prepared in Example 3 was tested by an ellipsometry and found to have a uniformity deviation of ±4.5%; a surface contact angle of 141°; after being kept at 200°C for 700 hours, the hydrophobic film showed no yellowing or cracking, and the contact angle remained at 139°; after being immersed in a NaOH solution at a depth of 2m and pH=14 for 168 hours, the hydrophobic film showed no cracking or peeling after removal, and the contact angle remained at 138°.

[0099] The hydrogen sensor was applied to monitor the hydrogen production concentration in real time during the alkaline water electrolysis process. The sensor has a detection error of ≤±1.8% within the detection range of 0-5 vol% H2 and a response time fluctuation of ≤0.5s within the detection temperature range of 2-120℃, meeting the stability requirements of practical applications.

[0100] Example 4

[0101] This embodiment is similar to Embodiment 1, except that the type of semiconductor material is adjusted to SnO2, and the remaining steps are performed in accordance with Embodiment 1.

[0102] The high-temperature alkaline corrosion resistant hydrogen sensor prepared in Example 4 was tested by an ellipsometry and found to have a uniformity deviation of ±5.2%; a surface contact angle of 138°; after being kept at 200°C for 700 hours, the hydrophobic film showed no yellowing or cracking, and the contact angle remained at 136°; after being immersed in a NaOH solution at a depth of 2m and pH=14 for 168 hours, the hydrophobic film showed no cracking or peeling after removal, and the contact angle remained at 134°.

[0103] The hydrogen sensor was applied to monitor the hydrogen production concentration in real time during the alkaline water electrolysis process. The sensor has a detection error of ≤±2.2% within the detection range of 0-5 vol% H2 and a response time fluctuation of ≤0.7s within the detection temperature range of 2-120℃, which meets the monitoring requirements under normal operating conditions.

[0104] Example 5

[0105] This embodiment is similar to Example 1, except that the types of hydrophobic silane precursor and semiconductor material are adjusted. In this embodiment, SnO2 is used as the semiconductor material. The treated Ru@SnO2-OH powder is immediately transferred to a vinyltriethoxysilane solution for hydrophobic film modification. The remaining steps are the same as in Example 1.

[0106] The high-temperature alkaline corrosion resistant hydrogen sensor prepared in Example 5 was tested by an ellipsometry and found to have a uniformity deviation of ±6.2%; a surface contact angle of 126°; after being kept at 200°C for 700 hours, the hydrophobic film showed no yellowing or cracking, and the contact angle remained at 122°; after being immersed in a NaOH solution at a depth of 2m and pH=14 for 168 hours, the hydrophobic film showed no cracking or peeling after removal, and the contact angle remained at 118°.

[0107] The hydrogen sensor was applied to monitor the hydrogen production concentration in real time during the alkaline water electrolysis process. The sensor has a detection error of ≤±3.5% within the detection range of 0-5 vol% H2 and a response time fluctuation of ≤1.2s within the detection temperature range of 2-120℃. It is suitable for working conditions where the requirements for detection accuracy are relatively relaxed.

[0108] Comparative Example 1

[0109] The difference between this embodiment and embodiment 1 is that no noble metal doping was performed, that is, no noble metal doping was performed in step (1), and the other steps are the same.

[0110] The hydrogen sensor prepared in Comparative Example 1 showed a uniformity deviation of ±4.4% as measured by an ellipsometry; a surface contact angle of 133°; and after 700 hours at 200°C, the hydrophobic film showed no yellowing or cracking, with a contact angle of 126°. After immersion in a NaOH solution at a depth of 2m and pH=14 for 168 hours, the hydrophobic film showed no cracking or detachment, and the contact angle remained at 126°.

[0111] The hydrogen sensor was applied to monitor the hydrogen production concentration in real time during alkaline water electrolysis. Within the detection range of 0–5 vol% H2, the detection error was ≤ ±10.1%, and within the detection temperature range of 2–120℃, the response time fluctuated by 4.7 s. This shows that although Comparative Example 1 can withstand high temperatures and alkaline solutions, its detection accuracy and response time are significantly reduced due to the lack of precious metal doping, making it unsuitable for applications requiring high detection accuracy.

[0112] Comparative Example 2

[0113] The difference between this embodiment and embodiment 1 is that hydrophobic film coating is not performed, that is, steps (2) to (4) are not performed.

[0114] The hydrogen sensor prepared in Comparative Example 2 showed a uniformity deviation of ±9.8% as measured by an ellipsometry; a surface contact angle of 56° (non-hydrophobic); after 700 hours at 200°C, surface cracking occurred, and the contact angle decreased to 45°; after immersion in a NaOH solution at a depth of 2m and pH=14 for 168 hours, surface cracking and peeling occurred upon removal, and the contact angle remained at 18°.

[0115] The hydrogen sensor was applied to monitor the hydrogen production concentration in real time during alkaline water electrolysis. Within the detection range of 0–5 vol% H2, the detection error was ≤ ±17.5%, and within the detection temperature range of 2–120℃, the response time fluctuated by 6.3 s. This demonstrates that Comparative Example 2, lacking a hydrophobic coating, could not isolate itself from corrosive media and therefore could not function properly under extreme conditions such as alkalinity.

[0116] Table 1: Test results of hydrogen sensors in Examples 1-5 and Comparative Examples 1 and 2

[0117]

[0118]

[0119] The hydrogen sensor provided by this invention constructs highly efficient hydrogen adsorption active sites on the surface of semiconductor materials by doping with noble metals, optimizing electron transport efficiency. Simultaneously, a hydrophobic film provides stable protection for the gas-sensitive layer, avoiding the influence of environmental interference on the sensing signal and ensuring the accuracy and reliability of the detection results. This hydrogen sensor exhibits excellent adaptability to extreme environments, accurately meeting the requirements of high-temperature and strongly alkaline conditions. It can operate stably within a temperature range of 2–120°C and can withstand alkaline environments such as potassium hydroxide, sodium hydroxide, sodium carbonate, and sodium bicarbonate solutions with a mass fraction of 0–50%. This effectively solves the performance degradation problems of traditional hydrogen sensors caused by irreversible damage to the microstructure of sensitive materials due to high temperatures, surface chemical corrosion caused by strong alkalis, and the formation of water films in aqueous environments that hinder hydrogen molecule adsorption. It meets the long-term monitoring needs in extreme scenarios such as alkaline water electrolysis for hydrogen production. Therefore, this invention effectively overcomes some practical problems in existing technologies, thus possessing high utilization value and practical significance.

[0120] The above embodiments are merely illustrative of the principles and effects of the present invention and are not intended to limit the invention. Any person skilled in the art can modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by those skilled in the art without departing from the spirit and technical concept disclosed in the present invention should still be covered by the claims of the present invention.

Claims

1. A hydrogen sensor, characterized by, The hydrogen sensor comprises: a ceramic substrate electrode; a gas sensitive layer arranged on the surface of the ceramic substrate electrode; wherein the gas sensitive layer comprises a composite material of a semiconductor material doped with a noble metal, and a hydrophobic film coated on the surface of the composite material, the hydrophobic film being formed by a chemical coupling reaction between a hydrophobic silane and a hydroxyl group.

2. The hydrogen sensor of claim 1, wherein, The semiconductor material comprises one or more of molybdenum disulfide, tin dioxide, titanium dioxide, zinc oxide, and indium oxide.

3. The hydrogen sensor of claim 1, wherein, The noble metal comprises one or more of ruthenium, gold, palladium, and platinum; and / or the doping amount of the noble metal accounts for 0.1wt%-5wt% of the mass of the semiconductor material.

4. The hydrogen sensor of claim 1, wherein, The hydrophobic silane comprises one or more of vinyltrimethoxysilane and vinyltriethoxysilane; and / or the contact angle of the hydrophobic film is greater than or equal to 90°, and the coating thickness of the hydrophobic film is 0-2μm.

5. The hydrogen sensor of claim 1, wherein, The hydrogen sensor further comprises a shell for packaging the ceramic substrate electrode and the gas sensitive layer.

6. A method for producing the hydrogen sensor as claimed in any one of claims 1 to 5, characterized by, The method comprises the following steps: dispersing a semiconductor material in a solvent, adding a noble metal salt solution and stirring to allow noble metal ions to be adsorbed on the surface of the semiconductor material, and then performing solid-liquid separation and drying to obtain a first precursor; performing hydroxylation treatment on the first precursor to introduce hydroxyl groups on the surface of the first precursor, thereby obtaining a second precursor; transferring the second precursor to a hydrophobic silane solution, adjusting the pH of the system to be alkaline, and stirring to allow the hydrophobic silane to react with the hydroxyl groups, thereby obtaining a gas sensitive material precursor coated with a hydrophobic film; firing the gas sensitive material precursor coated with the hydrophobic film in a reducing atmosphere to reduce and solidify the noble metal ions in the hydrophobic film, thereby obtaining a gas sensitive material coated with a hydrophobic film; preparing the gas sensitive material coated with the hydrophobic film into a slurry, and coating the slurry on the surface of a ceramic substrate electrode to obtain a hydrogen sensor.

7. The method of claim 6, wherein the hydrogen sensor is prepared by a method comprising: The hydroxylation treatment comprises any one of plasma treatment, alkali treatment, and hydrothermal method.

8. The method of claim 6, wherein the hydrogen sensor is prepared by a method comprising: The solvent comprises an organic solvent and / or deionized water, and the organic solvent comprises one or more of ethanol, acetonitrile, and isopropanol.

9. The method of claim 6, wherein the hydrogen sensor is prepared by a method comprising: 5 depositing a hydrogen sensing material on a substrate; and depositing a protective layer on the hydrogen sensing material. In the step of firing the gas sensitive material precursor coated with the hydrophobic film in a reducing atmosphere, the reducing atmosphere is a mixture of hydrogen and nitrogen, the volume ratio of hydrogen in the mixture is 1-30%, the reduction temperature is 100-500℃, and the reduction time is 4-12 hours.

10. Use of the hydrogen sensor according to any one of claims 1 to 5, characterized in that The hydrogen sensor is applied to hydrogen monitoring under extreme working conditions of high temperature and strong alkali; the hydrogen detection concentration range of the hydrogen sensor is 0-5vol%, and the hydrogen detection temperature is 2-120℃.